Importancia de la Lengua Inglesa como medio para la Internacionalización de la Universidad Nacional de Itapúa (Journal on studies and research of academic knowledge, 2019)
This research deals with the importance of the English language for internationalization and has as general objective to discriminate the importance of English as a linking language for the internationalization of National University of Itapúa; and as specific objectives; to determine the relevance of the use of English in the professional development of university students in the process of internationalization, to specify the value of the English language for the strengthening of mobility programmes from the perspective of those in charge of International Relations Departments of foreign universities; and to establish the importance of internationalization for the continuous development, improvement and progress of higher education. This study used a mixed methodology with an exploratory descriptive design. The sample was composed of students who participated in mobility programmes; heads of International Relations Departments at some universities abroad, and a researcher in the area of internationalization. The most relevant results showed that the English language occupies a preponderant role at universities and is highly important in order to achieve a relevant and adequate internationalization at National University of Itapúa, generating countless of opportunities at international level even for Spanish speaking countries. English favors the strengthening of links among universities and the professional development of university students because it opens doors to globalization; thus it is proposed to increase the level of English language teaching in all higher education careers, among other actions leading to the acquisition of the language.
Keywords: Internationalization; English language; higher education